PENGALAMAN KELUARGA DALAM MERAWAT PASIEN KANKER SERVIKS - Rizawati, Reflina Milenia (Jurnal Kesehatan Ilmiah Aufa Royhan, 2022)
Routine treatment of cervical cancer patients makes the family have to take care of it. This study aims to determine the family's experience in caring for cervical cancer patients. This study used a descriptive phenomenological design with a phenomenological approach. The research sample was 4 participants who were taken based on the inclusion criteria using a purposive sampling technique. Data collection using interview methods and the analysis used is thematic analysis. Participants know the signs and symptoms of the patient's illness during treatment, make treatment efforts such as medical and non-medical that make an impact on the patient. Participants' responses during the treatment were tired, sad, patient and sincere. Taking care of the patients themselves and the inactivity of carrying out routines became obstacles and challenges for participants. Support is not only provided by families but also health workers, neighbors and teachers. The experience gained by participants is that they have knowledge of disease and treatment, try to meet the needs of patients both biologically and psychologically, even though they have obstacles and challenges, but participants also have positive things from their experiences during treatment.